Term Sail Dalam Al-Qur’an (Analisis Semiotika Ferdinand De Saussure) - Rama, Ramadona (Al-Kauniyah : Jurnal Ilmu Alquran dan Tafsir, 2024)
The term Sail in the Qur'an, according to various studies, refers to “a beggar.” The practice of begging negatively impacts moral and ethical values in society, eroding integrity and honesty. This study aims to analyze the meaning of Sail in QS. Al-Baqarah verse 177 and QS. Ad-Dhuha verse 10, and to explore how the context and principles of semiotics can emphasize that the term Sail should not be interpreted as “beggar.” The objective is to uncover meanings relevant to current social issues and to examine the impact of begging practices that do not align with Islamic values.This research is qualitative, descriptive, and analytical, utilizing Ferdinand de Saussure’s semiotic approach. Primary data is derived from QS. Al-Baqarah verse 177 and QS. Ad-Dhuha verse 10. The findings of this study indicate that: firstly, in QS. Al-Baqarah verse 177, the meaning of Sail suggests that those who ask for help have rights to the wealth of the faithful, and that giving should be done sincerely and with love for Allah. Secondly, the meaning of Sail in QS. Ad-Dhuha verse 10 instructs Muslims not to rebuke or treat beggars harshly, whether in material terms or advice. This prohibition against harshness reflects an invitation to act with gentleness and compassion. Thirdly, interpreting Sail in the context of contemporary issues highlights the importance of social solidarity, integrity, and honesty, fostering a harmonious environment and providing meaning and purpose in life.Top of FormBottom of Form